Echa ‘dawnych’ podziałów w kontekście demokratycznych przemian w Irlandii Północnej i Republice Południowej Afryki. Analiza porównawcza na podstawie powieści Lucy Caldwell i Zoë Wicom - Bartnik, Ryszard (Przestrzenie Teorii, 2015)
The 1990s saw significant political changes in countries like South African or Northern Ireland. Prior to the revolutionary transformation, the structure of those societies was marked by a rigid bipolar configuration. However, after the political watersheds, what could be observed in the public domain was a turn towards reconciliation. Regardless of its traumatic character, the past was to yield to ‘prospect for the future’. It quickly transpired, however, that the key to deconstruct- ing the walls dividing the societies lay nowhere else but in the past. And it was the local literary field where a discussion on the weight of remembering what has seemingly come to an end was initiated. This paper tries to illustrate that debate by a comparative analysis of two novels represen- tative of the respective cultural contexts: Playing in the Light (2006) by Z. Wicomb and Where They Were Missed (2006) by L. Caldwell.